Insights into the High-Mass X-ray Binary Population of the Magellanic Clouds - Antoniou, V.; Zezas, A.; Hatzidimitriou, D.; Kalogera, V. (2013)
In contrast to the Small Magellanic Cloud (SMC), the Large Magellanic Cloud (LMC), our nearest starforming galaxy with metallicity between the Galaxy and the SMC, has received little attention in X-rays so far. With the aim to compare the accreting X-ray binary (XRB) populations in two of our nearest star-forming galaxies, we recently compiled the most complete census of high-mass X-ray binaries (HMXBs) in the LMC. We found 43 members of which 13 are XRB pulsars, while we also identified their most likely optical counterpart (previously, half of these sources lacked an identification). Using this census, we investigated the link between the young accreting XRBs and their parent stellar populations. It was known that HMXBs can be used as star-formation (SF) rate indicators, but these first studies have been focused only on bright systems (Galaxy: >1038 erg s-1, Magellanic Clouds: >1036 erg s-1) and SF values for the whole galaxy. By including Magellanic Cloud sources with X-ray luminosities at least two order of magnitudes fainter than the above limits and by utilizing the detailed, spatially resolved, SF history maps of these galaxies, we were able to provide observational constraints on ill-understood parameters related to their formation and evolution (such as the kick velocities imparted into the neutron star during the supernova explosion) and to derive their formation efficiency. This work was mainly supported by the National Aeronautics and Space Administration under Grant No. NNX10AH47G issued through the Astrophysics Data Analysis Program.